A genetic link between prepregnancy body mass index, postpartum weight retention, and offspring weight in early childhood. Issue 1 (24th November 2016) - Li, Aihua; Teo, Koon K.; Morrison, Katherine M.; McDonald, Sarah D.; Atkinson, Stephanie A.; Anand, Sonia S.; Meyre, David
Abstract : Objective: The effects of maternal prepregnancy body mass index (BMI) and gestational weight gain (GWG) on maternal and offspring obesity traits, as well as the maternal and offspring genetic contribution to GWG and postpartum weight retention, were examined. Methods: Blood samples from mothers ( n = 608) and offspring ( n = 541) were genotyped for 83 BMI‐associated SNPs and 47 waist‐to‐hip ratio (WHR)‐associated SNPs. Linear regression and mixed‐effects regression models were performed to examine clinical epidemiological and genetic associations with unweighted and weighted BMI and WHR genetic risk scores (GRS). Results: Prepregnancy BMI was positively associated with offspring weight and BMI Z ‐score from birth to 5 years. GWG was positively associated with maternal postpartum weight retention at 1 and 5 years and with offspring weight Z ‐score from birth to 5 years old. The maternal unweighted BMI GRS was associated with prepregnancy BMI, postpartum weight retention at 5 years, and offspring weight Z ‐score from birth to 5 years old, but not associated with GWG. Both maternal and offspring unweighted WHR GRSs were negatively associated with GWG. Conclusions: Maternal BMI‐associated SNPs may contribute to the genetic link between prepregnancy BMI variation, long‐term postpartum weight retention, and offspring birth weight and longitudinal weight. Maternal and offspring WHR‐associated SNPs may contribute to GWG variation.